Effect of Capital Structure, Firm Size and Dividend Policy on Firm Value in Manufacturing Companies - Didin Septian Mahardiana Suprayoga; Wisnu Panggah Setiyono (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of capital structure, firm size and dividend policy on firm value. Several previous studies on firm value showed different results. Therefore, other research needs to be done to retest the theory of firm value. The population of this study was 15 manufacturing companies. The sampling method used was purposive sampling method, so that 15 sample companies were obtained for 3 years of observation (2018 - 2020) with 45 observations (observations). The research data were obtained from sample companies which were downloaded from the Indonesia Stock Exchange website. The data analysis technique used is descriptive statistical analysis and multiple regression analysis. The process of data analysis carried out first is descriptive statistics, classical assumption test, multiple regression analysis and then hypothesis testing. The results of this study partially show that capital structure, firm size and dividend policy have a significant effect on firm value. The results of this study indicate that capital structure, firm size and dividend policy have a simultaneous effect on firm value. Keywords - Capital Structure, Firm Size, Dividend Policy and Firm Value